A Reference Genome Sequence for Giant Sequoia. Issue 11 (1st November 2020) - Scott, Alison D; Zimin, Aleksey V; Puiu, Daniela; Workman, Rachael; Britton, Monica; Zaman, Sumaira; Caballero, Madison; Read, Andrew C; Bogdanove, Adam J; Burns, Emily; Wegrzyn, Jill; Timp, Winston; et al.
Abstract: The giant sequoia ( Sequoiadendron giganteum ) of California are massive, long-lived trees that grow along the U.S. Sierra Nevada mountains. Genomic data are limited in giant sequoia and producing a reference genome sequence has been an important goal to allow marker development for restoration and management. Using deep-coverage Illumina and Oxford Nanopore sequencing, combined with Dovetail chromosome conformation capture libraries, the genome was assembled into eleven chromosome-scale scaffolds containing 8.125 Gbp of sequence. Iso-Seq transcripts, assembled from three distinct tissues, was used as evidence to annotate a total of 41, 632 protein-coding genes. The genome was found to contain, distributed unevenly across all 11 chromosomes and in 63 orthogroups, over 900 complete or partial predicted NLR genes, of which 375 are supported by annotation derived from protein evidence and gene modeling. This giant sequoia reference genome sequence represents the first genome sequenced in the Cupressaceae family, and lays a foundation for using genomic tools to aid in giant sequoia conservation and management.